Perancangan Automated Guided Vehicle Berbasis Arduino Sebagai Robot Pelayan di Kafe - Prawiraka Muhammad, Rey Akashi; Febamukti, Falah Akbar; Chandra, Pradipta Arya; Wibowo, Bagus Cahyo; Simanjuntak, Samuel Fredrick; Muslimin, Muslimin; Luqyana, Dhiya; Muhammad, Azam Milah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The café industry faces challenges in improving order delivery efficiency, especially during peak hours. The inability to provide fast and consistent service can reduce customer satisfaction and café competitiveness amidst intense competition. Automation technologies, such as robot waiters, offer potential solutions to address these issues. Therefore, this research aims to design an Arduino-based Automated Guided Vehicle (AGV), named “Robo Waiter” as an automated waiter robot to optimize order delivery. The research method uses a Quality Function Deployment (QFD) approach with a House of Quality (HoQ) matrix to integrate customer needs into the final product design and specifications. Interviews with 20 interviewees identified key needs such as operation stability, safety, and delivery efficiency. The Robo Waiter was designed with line tracking navigation, ultrasonic sensors, and a food-grade basket. The design is designed to improve operational efficiency with features according to customer needs. This research shows that an aesthetically pleasing and cost-effective Robo Waiter design can be an innovative solution to improve the competitiveness of cafes through the application of efficient automated technology with customized specifications to achieve the desired targets.